Implementation of an Integrated Information Network System Based on Indonesia One Search (IOS) in University Libraries - Eni Amaliah; Lufti, Adnan; Fadila, Nurul (Jurnal El-Pustaka, 2025)
This article examines the deployment of information network systems, namely the adoption of Indonesia One Search (IOS) in university libraries. The used methodologies include of literature reviews and online observations, designed to comprehensively analyze the implementation of IOS. A system is characterized as a collection of interacting components aimed at achieving certain objectives, while information is the outcome of data processing that serves a purpose for the receiver. This essay emphasizes the significance of cooperation among libraries in establishing efficient information networks. The text elaborates on many collaborative methods, including library acquisition, collection sharing, and inter- library lending. This partnership offers enhanced information access, resource efficiency, personnel specialization, and less material duplication. Indonesia One Search (IOS) is a unified search platform that consolidates collections from libraries, museums, archives, and electronic information sources across Indonesia. IOS, introduced by Ismail Fahmi, Ph.D., and overseen by the National Library of the Republic of Indonesia, seeks to provide extensive and accessible information for students and other users. The iOS development process includes bibliography compilation, text analysis, and anti-plagiarism services. The functionalities provided by iOS, like full-text search and interaction with digital library apps, illustrate its capacity to fulfill information requirements in the digital age. The use of IOS at institutions, including the Indonesian Education University and the Indonesian Islamic University, demonstrates its efficacy in enhancing students' knowledge retrieval skills. This study underscores the need for libraries to adapt to user requirements in the digital age and highlights the possibilities for cooperation across libraries to enhance services via technology.